Evolution of sexual size dimorphism in the wing musculature of Drosophila - Claire B. Tracy; Janet Nguyen; Rayna Abraham; Troy R. Shirangi (PeerJ, 2020)
Male courtship songs in Drosophila are exceedingly diverse across species. While much of this variation is understood to have evolved from changes in the central nervous system, evolutionary transitions in the wing muscles that control the song may have also contributed to song diversity. Here, focusing on a group of four wing muscles that are known to influence courtship song in Drosophila melanogaster, we investigate the evolutionary history of wing muscle anatomy of males and females from 19 Drosophila species. We find that three of the wing muscles have evolved sexual dimorphisms in size multiple independent times, whereas one has remained monomorphic in the phylogeny. These data suggest that evolutionary changes in wing muscle anatomy may have contributed to species variation in sexually dimorphic wing-based behaviors, such as courtship song. Moreover, wing muscles appear to differ in their propensity to evolve size dimorphisms, which may reflect variation in the functional constraints acting upon different wing muscles.